Application of stepping stones triple-P on parents of intellectually disabled adolescent with emotional and behavioral problems - Faizah, Firsta; Madjid, Erniza Miranda; Djuwita, Efriyani (Psychological Research and Intervention, 2022)
This study was conducted to determine the effectiveness of the Stepping Stones Triple-P (SSTP) intervention in a family of teenagers with moderate intellectual disability with emotional and behavioral problems. This intervention program aims to help prevent emotional and behavioral problems in children with moderate intellectual disability through positive parenting training. This intervention program is carried out in 9 sessions; each session lasts ± 60 – 120 minutes at each meeting and lasts ± three weeks, carried out online through the Zoom meeting. The intervention method in this study was implemented through lectures, discussions, worksheets, and roleplay methods. Children's behavior problems were measured using the Child Behavior Checklist (CBCL) and a diary of children's behavior filled in by parents during pre-post intervention and follow-up. The Parenting Sense of Competence Scale (PSOC) measures parents' perceptions of competence in parenting practices. This study's participants were the parents (mother) of a boy aged 16 years 4 months (N) diagnosed with moderate intellectual disability with emotional and behavioral problems. The results of this study indicate that the SSTP intervention program effectively reduces the emotional and behavioral problems shown by N by increasing the knowledge and skills of parents in implementing positive parenting strategies. In this study, there were positive changes in parenting practices applied by mothers to children, such as forming a harmonious and warm relationship between mothers and children. The positive changes achieved by mothers in implementing positive parenting also influenced the change in problematic behavior in children (N) to decrease and become more positive.